1982
DOI: 10.1159/000153321
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the Distribution of Adenosine Deaminase and Superoxide Dismutase Markers in Different Populations

Abstract: All previously published data on gene frequencies of the ADA and SOD systems are compiled in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
2

Year Published

1986
1986
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 36 publications
3
22
2
Order By: Relevance
“…Therefore, we chose a random control group consisting of consecutive newborns from the same population as the study group, which seems as nonbiased as possible. The frequency of ADA*2 allele in the control group (7.3%, 95% confidence interval: 5.1–10.2%) was similar to the values reported 30 years ago in two distinct Polish groups (8.9% in Lower Silesia and 6.0% in Krakow) [6], indicating the lack of significant population drift. It was also similar to other European Caucasian populations (Germany: 4.5–7.3%, Denmark: 5.6–6.7%, Hungary: 6.2–10.1%, Italy: 6.0–9.1%, Portugal: 5.5%) [6].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, we chose a random control group consisting of consecutive newborns from the same population as the study group, which seems as nonbiased as possible. The frequency of ADA*2 allele in the control group (7.3%, 95% confidence interval: 5.1–10.2%) was similar to the values reported 30 years ago in two distinct Polish groups (8.9% in Lower Silesia and 6.0% in Krakow) [6], indicating the lack of significant population drift. It was also similar to other European Caucasian populations (Germany: 4.5–7.3%, Denmark: 5.6–6.7%, Hungary: 6.2–10.1%, Italy: 6.0–9.1%, Portugal: 5.5%) [6].…”
Section: Discussionsupporting
confidence: 81%
“…The enzyme encoded by the A22 allele (described also as ADA*2 or ADA2) has about 35% less catalytic activity than enzyme encoded by G22 allele (ADA*1, ADA1), and individuals carrying one copy of ADA*2 allele display 15–20% lower activity compared to ADA*1 homozygotes [5]. ADA*2 allele is present in approximately 12% of Caucasians [6]. …”
Section: Introductionmentioning
confidence: 99%
“…The electrophoretic 2-1 1-1 1-1 1-1 5-1 1-1 1-1 1-1 1-1 5-1 1-1 2-1 1-1 1-1 Phenotype mobility was the same as that described for the first time by Detter et al [1970] and subsequently by others [Weissmann et al, 1982] and called ADA 5-1.…”
Section: Resultsmentioning
confidence: 57%
“…The fre quency of the A DA *2 allele ranges from 0.0018 to 0.138 [Weissmann et al, 1982], It has been demonstrated [Battistuzzi et Rogers and Hopkinson [1981] calculated that the enzymatic activity of the rare variants ADA IW and ADA 3 were 67 and 28%, respectively, of the enzyme activity of the common variant ADA I. Giblett et al [1972] described an asso ciation between the absence of erythro cytic ADA activity and an autosomal recessive form of severe combined immu nodeficiency disease (SC1D).…”
Section: Introductionmentioning
confidence: 99%
“…[28], with the exception of northern Sweden which has well-known strong finnish affin ities [29]. AK1, ADA.…”
Section: Gene Frequenciesmentioning
confidence: 99%